Crisis, temporality and governmental policy agendas: The cases of Finland and Sweden - Vogt, Henri; Värttö, Mikko (Wiley, 2025)
Crises transform the temporal orientation of political decision‐making. They demand
immediate and decisive action and thus convert time into a means of political control. In
these circumstances, assessing the long‐term consequences of proposed policies with
respect to welfare, sustainability or justice also becomes demanding. Yet crisis conditions
may also contain of elements that can enable positive postcrisis societal changes. Crises
can offer opportunities for new developmental measures and building a better future—
something political leaders may capitalise on in their agenda‐setting. By analysing the
programmes of the post‐2014 Finnish and Swedish governments, this paper seeks to
make sense of how the current crisis mode has shaped these countries' politics in terms of
their temporal horizons. The analysis focuses on three main perspectives or forms
of articulation—innovative stabilisation, long‐termism and synchronisation—by way of
which these governments seek to navigate through crises‐afflicted times and offer a
desirable future direction for their respective societies. The analysis offers important
insights into the (unused) potential of crises to achieve something substantially novel in
the Nordic and European political landscape, ultimately advancing the conditions for a
future‐regarding democratic system.